2002
DOI: 10.1038/sj....bjc.6600183...
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of cyclooxygenase-2 induces cell-cycle arrest in the epithelial cancer cell line via up-regulation of cyclin dependent kinase inhibitor p21

Abstract: Cyclooxygenase-2 is the rate-limiting enzyme in synthesis of prostaglandins and other eicosanoids. Prior reports have shown that inhibition of cyclooxygenase-2 activity, either by selective inhibitors or by antisense oligonucleotide, results in suppression of growth of squamous cell carcinoma cell lines which express high cyclooxygenase-2 levels, such as NA, a cell line established from a squamous cell carcinoma of the tongue. To investigate the mechanisms by which cyclooxygenase-2 inhibitors suppressed growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Selective COX-2 inhibitors suppress growth of cells by inducing G0/G1, cell-cycle arrest and thus apoptosis 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Selective COX-2 inhibitors suppress growth of cells by inducing G0/G1, cell-cycle arrest and thus apoptosis 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Another large population-based survey reported that the use of NSAIDs significantly reduced the risk of both gastric and oesophageal carcinoma (Farrow et al, 1998). Although the precise mechanisms by which NSAIDs, and COX-2 selective inhibitors in particular, modulate tumour growth have not been elucidated, it appears that cell cycle arrest and apoptosis may play a critical role (Chang and Weng, 2001;Grosch et al, 2001;Cheng et al, 2002;Joe et al, 2002;Kundu et al, 2002;Toyoshima et al, 2002). Alternatively, Sawaoka et al (1998) and Tsujii et al (Tsujii and DuBois, 1995;Sawaoka et al, 1998;Tsujii et al, 1998) have suggested that a decrease in angiogenesis may account for the inhibitory properties of COX-2 selective NSAIDs on tumour growth.…”
Section: Discussionmentioning
confidence: 99%
“…Celecoxib, an inhibitor of cyclooxygenase-2 (COX-2), may prevent CRC, and even prohibits the growth of tumor cells, through the inhibition of angiogenesis, apoptosis and blockage of the cell cycle (13)(14)(15). However, to date, its exact anti-cancer mechanism in malignant neoplasms, including CRC, is poorly understood.…”
Section: Microrna Expression Pattern and Its Alteration Following Celmentioning
confidence: 99%